Exploring economic effects of work out of company office based on bibliometric analysis - Petcu, Monica Aureliana; Cișmașu, Irina Daniela (Journal of Business Economics and Management, 2023)
Increasing the incidence of work out of company office (WOCO) by transforming it from a more limited and circumstantial practice into a predominant work option requires a special attention of social partners and political decision-makers in order to harmonize economic and social performances. The aim of this research is to evaluate the effects of WOCO from the economic perspective – resources allocation and performance, developing the previous studies through the approach of the broad area of WOCO, extending the analysis at the microeconomic and macroeconomic level, in order to harmonize the objectives of sustainable economic growth. Using bibliometric techniques, the 289 scientific publications from the Web of Science platform were analysed, highlighting the conceptual and intellectual structure of the research, in the field. The research themes related to economic topic consist of: the degree of employment, technology and digital infrastructure development, economic performance and productivity, and carrying out economic activities from the perspective of WOCO. The results of this broad-spectrum research reveal a holistic view of the network, constituting a relevant reference to develop a comprehensive understanding of the impact of WOCO, useful to researchers, managers, and regulatory bodies, and identifying the potential research gaps and future research direction.